The Domestic Considerations of Indian Foreign Policy: A Case Study of Indo-Bangladesh Teesta Water Deal during UPA-II Government - Nihar Kanti Baidya (Integrated Journal for Research in Arts and Humanities, 2022)
The foreign policy of a country is shaped and influenced not only by the necessity of international environment but also by imperatives of domestic structures and processes. The focus area of the study is primarily Indo-Bangladesh Teesta water deal during UPA-II government. Teesta basin is confronted with a wide range of challenges covering economics, government, and politics to culture, the environment to gender issues to security issues to the health of riverine ecosystems. These concerns, while differing in degree and type, are all tied together by the Teesta, which functions as a common thread flowing through them all and connects them all together. Even though the basin is best known for the lack of a bilateral agreement between India and Bangladesh over water sharing, internal disputes such as the anti-dam motion in Sikkim and the 'Save the Buri Teesta' movement in Bangladesh are also big concerns tied to bilateral trade between the two riparian countries. The study concentrated on the geopolitics of water conflicts in the Teesta basin as well as the role that the TMC party as a domestic factor has played in water negotiations in recent years. The concern of the paper is to examine how a internal domestic considerations of a country act in shaping a country’s foreign policy.